An anatomical and functional topography of human auditory cortical areas - Moerel, Michelle; De Martino, Federico; Formisano, Elia (Frontiers in Neuroscience, 2014)
While advances in magnetic resonance imaging (MRI) throughout the last decades have enabled the detailed anatomical and functional inspection of the human brain non-invasively, to date there is no consensus regarding the precise subdivision and topography of the areas forming the human auditory cortex. Here, we propose a topography of the human auditory areas based on insights on the anatomical and functional properties of human auditory areas as revealed by studies of cyto- and myelo-architecture and fMRI investigations at ultra-high magnetic field (7 Tesla). Importantly, we illustrate that - whereas a group-based approach to analyze functional (tonotopic) maps is appropriate to highlight the main tonotopic axis - the examination of tonotopic maps at single subject level is required to detail the topography of primary and non-primary areas that may be more variable across subjects. Furthermore, we show that considering multiple maps indicative of anatomical (i.e. myelination) as well as of functional properties (e.g. broadness of frequency tuning) is helpful in identifying auditory cortical areas in individual human brains. We propose and discuss a topography of areas that is consistent with old and recent anatomical post mortem characterizations of the human auditory cortex and that may serve as a working model for neuroscience studies of auditory functions.